Legal Implications of Not Performing Roya Fiduciary Guarantee by the Creditor - Kanishka Bhuller; Tan Kamello; Rosnidar Sembiring; Yefrizawati Yefrizawati (Locus Journal of Academic Literature Review, 2023)
The purpose of this research is to find out and analyze the obstacles of the creditor not doing roya fiduciary when the debtor's debt is paid off, legal protection to the debtor if the creditor does not do roya fiduciary guarantee and the legal implications of not doing roya fiduciary at PT Verena Multi Finance Medan City. This type of research is normative juridical legal research, the nature of the research is descriptive analysis, the techniques used are library research and field research. The results of the study state that the obstacles of creditors in carrying out fiduciary security roya are constraints on the removal system and constraints on legal arrangements. Legal protection to the debtor if the creditor does not make a fiduciary guarantee roya is stated in Article 25 paragraph (3) of the Fiduciary Guarantee Law that upon the abolition of the fiduciary guarantee the fiduciary recipient notifies the Fiduciary Registration Office of the abolition of the fiduciary guarantee by attaching a statement regarding the abolition of debt. The legal implication of not doing fiduciary roya at PT Verena Multi Finance Medan City is that the object of fiduciary guarantee that has not been royaed cannot be used as collateral if the object of the guarantee is to be re-guaranteed as an object of fiduciary guarantee, then the object must be royaed first.